Worlds Apart? Worlds Aligned? The Perceptions and Prioritizations of Civil Servant Values Among Civil Servants From China and The Netherlands. Issue 1 (2nd January 2016) - Yang, Lijing
Abstract : This study investigates the perceptions and prioritizations of five key civil servant values, based on in-depth qualitative interviews among 22 Chinese and 20 Dutch civil servants. It shows that Chinese and Dutch respondents interpret loyalty differently, referring respectively to the political party and to the organization. The common difficulty in upholding people-orientedness in practice is attributed to different reasons. Both view full transparency as unnecessary, and similarly, both value effectiveness more important than efficiency. This study offers substantial insight into civil servant values and a new perspective on cross-cultural value studies, along with implications for relevant research and practice.